Effects of Low-Temperature Stress During Anthesis Stage on Dry Matter Accumulation and Yield of Winter Wheat - Xiaodong Jiang; Qiuhui Chen; Evgenios Agathokleous; Jianqu Zhang; Zaiqiang Yang; M’Ponkrou Takin (Agronomy)
Wheat growth is highly sensitive to temperature fluctuations, and with the intensification of global climate change, low-temperature stress has become more frequent during various growth stages of wheat, severely affecting its growth and reducing wheat yield. An experiment examined the effects of low-temperature (daytime 8:00–20:00/nighttime 20:00–next day 8:00: 16 °C/8 °C, 12 °C/4 °C, 8 °C/0 °C, and 4 °C/−4 °C) and exposure durations (1, 3, and 5 days) on winter wheat yield during the anthesis stage. Compared to exposure duration, temperature was the main factor affecting dry matter accumulation, distribution, and transport. Temperature had an average influence of 79.7%, 57.5%, 61.9%, and 79.0% on dry matter distribution in the stem-sheath, leaf, spike axis+glume, and grain, respectively. It also affected pre-anthesis translocation amount, the contribution of pre-anthesis translocation to grains, post-anthesis accumulation amount, and the contribution of post-anthesis accumulation to grains by 48.3%, 55.1%, 44.2%, and 48.2%, respectively. Conversely, exposure duration mainly influenced grain-filling parameters, with an average effect of 43.8%, 44.0%, 83.3%, and 43.8% on the maximum filling rate, average filling rate, filling rate in the fast-increasing period, and filling rate during the slow growth period, respectively. Low-temperature duration also significantly altered the fast-increasing period, slow growth period, and grain weight per spike by 79.9%, 79.9%, and 51.3%, respectively. Low-temperature stress alters the accumulation and distribution of dry matter in wheat, and the duration of exposure further affects the grain-filling process, ultimately resulting in a decrease in yield.